Nitrate supplementation and athletic performance: a narrative review - Isabela Cristina Pimenta Amancio; Isabela Antonucci Pimenta Dias; Elizandra Milagre Couto; Wilson César de Abreu (Revista Brasileira de Prescrição e Fisiologia do Exercício)
This narrative review investigates the impact of nitrate supplementation on physical performance across endurance, intermittent, and strength exercises. Nitrate, ingested through beetroot juice, has shown potential ergogenic benefits, including enhanced vasodilation, mitochondrial efficiency, and muscle contractility. Studies indicate that nitrate supplementation can improve time trial performance, power output, and reduce oxygen cost in endurance exercises. For intermittent and strength exercises, findings suggest increased repetitions, total weight lifted, and reduced muscle fatigue. However, variability in study designs, participant characteristics, supplementation protocols, and exercise modalities contribute to mixed results. Additionally, many studies suffer from small sample sizes and short durations, limiting the ability to draw definitive conclusions about long-term effects and safety. Placebo effects and individual variability further complicate the interpretation of results. While some studies suggest clear performance enhancements, the precise mechanisms remain unclear. Furthermore, most research predominantly involves male participants, highlighting the need for studies on female athletes. Future research should focus on standardizing protocols, increasing sample sizes, and exploring personalized supplementation strategies. Overall, nitrate supplementation through beetroot juice presents a promising, evidence-based approach to enhancing various aspects of athletic performance, but further investigation is needed.